Development of an anti-rat complement C2 antibody that improves renal outcome in a rat kidney transplant model - Bracke, Laura; Delaere, Jolien; Haspeslagh, Eline; De Winter, Karen; Driege, Yasmine; Bilgraer, Raphael; Delahaye, Tim; Hack, C. Erik; Van de Walle, Inge (Frontiers in Immunology, 2026)
BackgroundPreviously we reported on the therapeutic monoclonal anti-human C2 antibody empasiprubart that inhibits activation of the classical and lectin pathways of complement. Preclinical studies with this antibody are hampered by its low affinity for C2 of animal species other than primates.Methods and resultsWe developed a high affinity, Ca2+-dependent anti-rat C2 antibody using the sequences and structural data of empasiprubart. Pharmacokinetics and pharmacodynamics of the resulting antibody in Sprague Dawley rats were assessed and used for an intervention study in a rat model of delayed graft function following kidney transplantation. The anti-rat C2 antibody improved kidney function and health in the rats within the first 2 weeks post-transplantation.ConclusionOur study shows the successful development of an analogue of empasiprubart that can be used in preclinical in vivo disease models and highlights the potential of C2-blocking as a therapeutic strategy for preventing delayed graft function following kidney transplantation.